"I never felt targeted as an Asian … until I went to a gay pub": Sexual racism and the aesthetic geographies of the bad encounter. (April 2017) - Ruez, Derek
Encounters across difference—in city spaces marked by diverse migration trajectories, cultural differences, and racialized hierarchies—have captured the attention of urban scholars concerned with both the challenge of "living with difference" and the promise of multicultural conviviality that inhere in the super-diversity of many cities. Expanding on approaches that focus on analyzing the conditions of a good or "meaningful" encounter that can reduce prejudice or promote intercultural understanding, this paper brings interviews with queer Asian men in Sydney, Australia into dialogue with Sara Ahmed's revaluation of the "bad encounter." It shows how research on encounters can more productively engage with how negative encounters can become meaningful political occasions in their own right. Focusing on the problem of sexual racism as it emerges in accounts shared by participants, the paper highlights dating and sex as important moments through which the aesthetic orderings of race, gender, and sexuality shape the unevenly shared spaces of citizenship and urban life.